3/2 divided 1/4=n then n is between

Answers

Answer 1
Answer: 3/2 ÷ 1/4= n 

n(3/2) (4/1) = n 

n= 12÷2 

Which gives you six



Related Questions

What is the perimeter of a trapezoid having side lengths of 20 ft, 20 ft, 26 ft and 18 ft?
AA, BBB, and CCC are collinear, and BBB is between AAA and CCC. The ratio of ABABA, B to BCBCB, C is 1:21:21, colon, 2. If AAA is at (7,-1)(7,−1)left parenthesis, 7, comma, minus, 1, right parenthesis and BBB is at (2,1)(2,1)left parenthesis, 2, comma, 1, right parenthesis, what are the coordinates of point CCC?
If it takes 16 faucets 10 hours to fill 8 tubs, how long will it take 12 faucets to fill 9 tubs?
Simplify 2(5x-3)-(2x+4), 24x-12y+40÷4, (2x)(3y)+2(-xy)
Mr. Jordan has 13 ponies. Each of his ponies eats 26 pounds of food each day. How many pounds of food do the ponies eat altogether each day? A. 338 pounds B. 104 pounds C. 39 pounds D. 2 pounds

What is 1/9 of 63% of $6,000?

Answers

Answer:

The answer is $420

Step-by-step explanation:

The procedure is multiply the number 6000 by 63% and (1)/(9). The order of these multiplying doesn't matter.

The percentage number can be changed into a fraction number following the next rule:

Give a x number in a range from 0 to 100:

x%=(x)/(100)

So,

63%=(63)/(100)=0.63

(1)/(9)*0.63*6000=420

Finally, the answer is $420

The answer is $420. Multiply 6,000 by 0.63 to find 63% of 6,000. That gives you 3780. Then to find 1/9 of 3780, divide it by 9. The answer is 40.
Hope that helped.

Jose wants to find the perimeter of triangle ABC. He uses the distance formula to determine the length of AC. Finish Jose’s calculations to find the length of AC.AC=square root<(-2-3)^2 +(6-2)
=square root<(-5)^2+(4)^2

What is the perimeter of triangle ABC? Round the answer to the nearest tenth, if necessary

Answers

Given:
AC = √(-2-3)² + (6-2)²
AC = √ -5² + 4²
AC = √ 25 + 16
AC = √41
AC = 6.40

I am assuming that the triangle is an equilateral triangle. This means that all sides are equal.

AC = AB = BC

Perimeter = 6.40 * 3 sides = 19.20
AC = √[(-2-3)^2 + (6-2)^] = √[5^2 + 4^2] = √[25+16] = √41 =6.4

To find the perimeter you need the lengths of AB and BC.

You already know the points (-2,6) and (3,2)

Then you need the point B to apply the distance formula from B to each of those points.

4 hundreths equals how many thousandths?

Answers

.04 =.040
 because u just add a 0at the hnd

Answer:

.04 .40 is the answer

Step-by-step explanation:

45 – 15 – 15 =
A. 15.
B. 0.
C. 1.
D. 30

Answers

The result of the expression 45 - 15 - 15 is 15.

(Option A).

What is the solution of the expression?

The solution of the linear expression is calculated as follows;

The given expression;

45 – 15 – 15 = ?

To solve the expression 45 - 15 - 15, we follow the order of operations, which dictates that we perform the subtraction operations from left to right.

First, we subtract 15 from 45:

45 - 15 = 30

Then, we subtract another 15 from the result of the previous operation:

30 - 15 = 15

Therefore, the result of the expression 45 - 15 - 15 is 15.

Therefore, the correct option is A. 15.

Learn  more about expressions here: brainly.com/question/723406

#SPJ6

45 - 15 - 15 = 45 - 30

45 - 30 = (15)

Tax" is an added amount when finding the grand total of a bill. True or false

Answers

Answer:

Step-by-step explanation:

True

Answer:

True.

Step-by-step explanation:

PLEASE HELP!!!!! 15 PTSExplain how the Quotient of Powers was used to simplify this expression. (2 points)
2^5/8 = 2^2

By finding the quotient of the bases to be,1/4 and cancelling common factors
By finding the quotient of the bases to be, 1/4 and simplifying the expression
By simplifying 8 to 2^3 to make both powers base two, and subtracting the exponents
By simplifying 8 to 2^3 to make both powers base two, and adding the exponents

Answers

quoteint of powers
(x^m)/(x^n)=x^(m-n)

we know that 8=x^3

so
(2^5)/8=2^2 can be rewritten as
(2^5)/(2^3)=2^2
and 5-3=2 so it's true

answer is
third one
by simplifieng 8 to 2^3 to make both powers base two, and subtraction the exponents
First, let's write the expression using numbers 

(2^5)/8 = 2^2 

Now, 8 = 2^3. So we can sub 

(2^5)/(2^3) = 2^2 

Now, there's a rule that states that (a^m)/(a^n) = a^(m-n) 

so (2^5)/(2^3) = 2^(5-3) = 2^2 

So the statement stands. 

The answer is C